Pelatihan Perencanaan dan Pengendalian Biaya dalam Mendukung Profitabilitas pada Gregors Barbershop di Kota Batam - Puspita Rama Nopiana; Fisna Mega Delima Laia; Santriati Bako (Lembaga Pengembangan Kinerja Dosen, 2026)
The management of material and labor costs at Gregors Barbershop is still manual and not formally structured, resulting in wastage of consumable materials, suboptimal labor utilization, and difficulties in determining service prices that align with the expected profit margins. Material costs, such as hair gel, tissues, disposable razors, and alcohol/disinfectants, are not recorded systematically, leading to frequent mismatches between stock and actual needs, while labor costs are calculated improvisationally without considering productivity and service targets. This activity aims to improve the ability of owners and employees to plan, control, and evaluate operational costs systematically, ensuring efficiency, resource optimization, and business profitability. The method uses an applied, hands-on approach, including the identification of partner needs, preparation of relevant training modules, direct operational mentoring, and evaluation with follow-up. The object of the activity is Gregors Barbershop in Batu Aji District, Batam City, which offers services such as modern men’s haircuts, classic shaves, shaving, hair treatments, and the sale of grooming products like pomade and hair oil. The results show increased efficiency in the use of consumable materials, more productive labor management, more systematic cost planning, and the ability to set service prices in line with costs and profit margins. It is recommended to implement a digital recording system and productivity-based incentives to ensure more accurate cost control, more efficient operations, and sustainable business profitability.